2010
DOI: 10.1007/s11892-010-0128-0
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Foot Disease in People with Advanced Nephropathy and Those on Renal Dialysis

Abstract: Among the spectrum of risk for diabetic foot disease conferred by chronic kidney disease (CKD), end-stage renal disease (ESRD) has emerged as a novel independent risk factor. Apart from the classical triad of neuropathy, infection, and peripheral arterial disease that operate in these individuals, the risk is further compounded by inadequate foot self-care by patients and by dialysis centers not providing onsite foot care, as medical priorities are diverted to the dialysis itself. Consequently, the burden of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 61 publications
4
64
2
3
Order By: Relevance
“…While 10.35% (12 patients) had ESRD requiring hemodialysis in our study, this had no statistical significance for lower extremity amputation or mortality. This finding differs from the current literature which shows generally poorer outcomes with both amputation and mortality in patients with renal disease 18 and this difference may be accounted for by individualized patient characteristics and surgical selection criteria based on the complexity of CN in patients with more advanced renal disease.…”
Section: Discussioncontrasting
confidence: 99%
“…While 10.35% (12 patients) had ESRD requiring hemodialysis in our study, this had no statistical significance for lower extremity amputation or mortality. This finding differs from the current literature which shows generally poorer outcomes with both amputation and mortality in patients with renal disease 18 and this difference may be accounted for by individualized patient characteristics and surgical selection criteria based on the complexity of CN in patients with more advanced renal disease.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study were generally in agreement with those of previous reports. [23][24][25][26] TASC II recommends that factors that can negatively affect wound healing, such as cardiac failure or poor nutritional status, should be evaluated and treated appropriately.…”
Section: Discussion What Difference Does This Study Make?mentioning
confidence: 99%
“…As chronic kidney disease progresses, the results also worsen and outcomes for patients on dialysis are very poor. 25,26,[28][29][30] A metaanalysis of the results of revascularization using venous grafts revealed that the 5-year amputation-free rate for the lower limb was 67% and the survival rate was 25% in patients on dialysis. 31 Dialysis also was the most important risk factor in our study population.…”
Section: Discussion What Difference Does This Study Make?mentioning
confidence: 99%
“…The risk factors may negatively influence the decision to perform a revascularization procedure [22]. However, our data indicate that even patients with increased risk factors may have favorable results [23]. Our study further establishes the advantages of early revascularization in diabetic patients who have critical limb ischemia requiring revascularization.…”
Section: Discussionmentioning
confidence: 53%